Perancangan Ulang Visual Brand Oli Green Zoil - Samuel Williem Arthur Phillips Wibowo; Siti Hadiati Nugraini (CITRAKARA, 2026)
Green Zoil is a lubricant oil product specially formulated for optimal engine performance. With superior additives, this oil promises maximum engine performance, component protection, cost-effective maintenance, and high efficiency. However, the Green Zoil logo is currently considered outdated and bears a resemblance to other brands’ logos; therefore, a redesign of its visual identity is necessary. This study employs qualitative methods through interviews, observations, and literature reviews. Analysis utilizes David E. Carter’s logo analysis method, the SWOT matrix, and brainstorming analysis. The design process follows Robin Landa’s five-stage design process: Orientation, Analysis, Concepts, Design, and Implementation. The results of this design project include the brand’s visual identity in the form of a Brand Identity Manual, a Graphic Standards Manual (GSM), and various other supporting materials.